The Monoterpenoid Perillyl Alcohol: Anticancer Agent and Medium to Overcome Biological Barriers - Thomas C. Chen; Clovis O. da Fonseca; Daniel Levin; Axel H. Schönthal (MDPI AG, 2021)
Perillyl alcohol (POH) is a naturally occurring monoterpenoid related to limonene that is present in the essential oils of various plants. It has diverse applications and can be found in household items, including foods, cosmetics, and cleaning supplies. Over the past three decades, it has also been investigated for its potential anticancer activity. Clinical trials with an oral POH formulation administered to cancer patients failed to realize therapeutic expectations, although an intra-nasal POH formulation yielded encouraging results in malignant glioma patients. Based on its amphipathic nature, POH revealed the ability to overcome biological barriers, primarily the blood-brain barrier (BBB), but also the cytoplasmic membrane and the skin, which appear to be characteristics that critically contribute to POH's value for drug development and delivery. In this review, we present the physicochemical properties of POH that underlie its ability to overcome the obstacles placed by different types of biological barriers and consequently shape its multifaceted promise for cancer therapy and applications in drug development. We summarized and appraised the great variety of preclinical and clinical studies that investigated the use of POH for intranasal delivery and nose-to-brain drug transport, its intra-arterial delivery for BBB opening, and its permeation-enhancing function in hybrid molecules, where POH is combined with or conjugated to other therapeutic pharmacologic agents, yielding new chemical entities with novel mechanisms of action and applications.